THE EFFECT OF ABDOMINAL MASSAGE ON CONSTIPATION IN STROKE PATIENTSATGRANDMED LUBUK PAKAM HOSPITAL IN 2023 - Simarmata, Juni Mariati; Maulina, Ridha (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Abdominal massage is a very effective intervention in overcoming constipation, besides that this therapy also does not cause dangerous side effects because it is a non-invasive action, can be done by the patient himselfand relatively inexpensive. The purpose of this study wasto determine the constipation score before and after abdominal massage. This study used a quantitative research design with a one group pretest-posttest design model, namely before the implementation of the sample observation was made and after the treatment was re-observed. Based on the resulting probability of 0.001. This means the probability <level of significance (? = 0.05), so Ha is accepted and H0 is rejected. Thus, it can be stated that there is a significant difference between constipation in stroke patients before abdominal massage (Pretest) and constipation in stroke patients after abdominal massage (Posttest). There is an Effect of Abdominal Massage on Constipation in Stroke Patients at Grandmed Lubuk Pakam Hospital in 2023.